2014
DOI: 10.1080/09168451.2014.890030
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis and characterization of new small serum proteins from the serum of a venomous snake (Gloydius blomhoffii)

Abstract: Some snakes have several anti-toxic proteins in their sera that neutralize their own venom. Five new small serum proteins (SSPs) were isolated from Japanese mamushi (Gloydius blomhoffii) serum by gel-filtration and RP-HPLC, and their N-Terminal sequences were determined. The amino acid sequences of the precursor proteins were deduced from the nucleotide sequences of cDNAs encoding them. Due to the sequence similarity to those of SSPs in habu snake (Protobothrops flavoviridis) serum (>75% identity), thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Mamushi venom consists of a variety of multiple enzymes that work as hemolytic toxins, including phospholipase A2, neurotoxins, and an alpha-toxin/a beta-toxin, that increase vascular permeability. Moreover, the venom contains arginine ester dehydrogenase that causes rhabdomyolysis, endopeptidase/bleeding factor (HR1 and HR2) that causes platelet aggregation, and L-amino acid oxidase 3 , 4 , 5 , 6 , 7 , 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Mamushi venom consists of a variety of multiple enzymes that work as hemolytic toxins, including phospholipase A2, neurotoxins, and an alpha-toxin/a beta-toxin, that increase vascular permeability. Moreover, the venom contains arginine ester dehydrogenase that causes rhabdomyolysis, endopeptidase/bleeding factor (HR1 and HR2) that causes platelet aggregation, and L-amino acid oxidase 3 , 4 , 5 , 6 , 7 , 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Even though the previously mentioned C -terminal deletion did not affect cMSF anti-hemorrhagic activity, the authors demonstrated that cMSF has a lower thermal stability limit (60 °C) when compared to HSF (100 °C) [ 56 ]. Shioi and colleagues also managed to purify SSPs from the serum of the Japanese mamushi that, as above discussed for HSF, interacted with jMSF in a yet to be described mechanism [ 57 ].…”
Section: Biochemical Backgroundmentioning
confidence: 99%